1999
DOI: 10.1007/s002110050401
|View full text |Cite
|
Sign up to set email alerts
|

A penalization method to take into account obstacles in incompressible viscous flows

Abstract: From the Navier-Stokes/Brinkman model, a penalization method has been derived by several authors to compute incompressible Navier-Stokes equations around obstacles. In this paper, convergence theorems and error estimates are derived for two kinds of penalization. The first one corresponds to a L 2 penalization inducing a Darcy equation in the solid body, the second one corresponds to a H 1 penalization and induces a Brinkman equation in the body. Numerical tests are performed to confirm the efficiency and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
646
1
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 717 publications
(670 citation statements)
references
References 11 publications
(14 reference statements)
13
646
1
10
Order By: Relevance
“…where the √ η behavior is consistent with previous studies [1,7]. In order to discretize (1.3), it is possible to use a Fourier pseudo-spectral method, where collocation on a regular grid of N points is used to evaluate the product χv.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…where the √ η behavior is consistent with previous studies [1,7]. In order to discretize (1.3), it is possible to use a Fourier pseudo-spectral method, where collocation on a regular grid of N points is used to evaluate the product χv.…”
supporting
confidence: 80%
“…Due to this analogy, the method is sometimes called Brinkman penalization. It has been mathematically justified in academic cases [1,7], and its use has rapidly spread to various domains of scientific computing.…”
mentioning
confidence: 99%
“…It can be shown that the solution of problem (42) converges slowly to the solution of the full Navier-Stokes problem in the channel domain as η → 0. 6 By plotting the tangential velocity as a function of strain rate at the channel wall location, Nguyen van yen, Farge, and Schneider 1 show that the penalisation method can be used to approximate noslip boundary conditions. More specifically, they demonstrate that their results are close to those for a Navier boundary condition with slip length s L approximately equal to 4/Re.…”
Section: B Comparison Of the Penalisation Methods With The Influence mentioning
confidence: 99%
“…A description of the numerical method can be found in Kolomenskiy et al (Kolomenskiy et al, 2011). Briefly, the no-slip boundary condition at the solid boundary is modeled using the volume penalization method (Angot et al, 1999). The penalized Navier-Stokes equations are solved using a classical Fourier pseudo-spectral method, the computational domain being therefore a rectangular box with periodic boundary conditions imposed at its six faces.…”
Section: Tests Of Force Balancementioning
confidence: 99%